PENGARUH DUKUNGAN ATASAN, KEJELASAN TUJUAN, DAN PELATIHAN TERHADAP PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH PADA ORGANISASI PERANGKAT DAERAH KABUPATEN BANYUWANGI - Sedianingsih, Sedianingsih; Safitri, Yunita Eka; Sinulingga, Rizky Amalia (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2020)
The purpose of this study is to examine the effect of supervisor support on the implementation of Regional Financial Accounting Systems (SAID). This study usea quantitative method using primary data in the form of questionnaires. Questionnaires amounting to 100 were distributed to employees of the regional apparatus organization in Banyuwangi district who held positions as heads of agencies, secretaries, and finance departements. The results of the respondent's answers from filling out the questionnaire were processed using partial least square (PLS)analysis using the Smart PLS application.The results of this study indicate that supervisor support influences the implementation of AND, clarity of purpose does not affect the implementation of SAKD, and training affect the implementation of SAKD.The results of this study are expected to be a source of consideration and input for the local government on how organizational behaviour can influences SAKD to provide a transparent and accountable information. Supervisor support and training can support employees to generate financial reportswithin providing resources (systems) to facilitate their work.